SISTEM PROGRAM SMART GATE BERBASIS INDIKATOR SUHU DAN WASTAFEL OTOMATIS - Islamiyah, Mufidatul; Arifin, Samsul; Anam, Rofiul (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2021)
This study discusses the system to overcome the current problems, namely the lack of discipline in washing hands and checking body temperature before entering the building which is one of the important things in implementing health protocols during the covid-19 pandemic. Both of these things are still often violated and are things that are often underestimated by visitors and the lack of firmness by officers in responding to these violations. In this study, a tool is designed to be used to check temperature and wash hands automatically which later will be an indicator to open a gate or automatic portal as a path or entrance to a building/building which is expected to be able to help officers work to be more disciplined. visitors who do not apply the health protocols that have been determined and are also able to minimize direct physical contact that will be caused by the current conventional system so as to minimize the risk of transmission of covid19. This tool uses a temperature sensor gy906/mlx 90614 as a non-contact temperature sensor and uses ultrasonic as a temperature sensor. Object distance detection, and also uses a dc motor actuator as a driver to open or close the gate. In the testing of the tools that have been carried out, the results obtained that the automatic gate system is able to run well by being controlled by both indicators, namely the temperature sensor and automatic sink as the main input in the whole system.